The Accumulative Effect of Heavy Metals on Liver and Kidney Functions (Medico Legal Update, 2021)
Some of the heavy metals exist in the outer layer of the earth, which is utilized for different economic andmanufacturing objectives. As some of these minerals impact humans in several ways, which are direct andindirect, others like Cadmium and Zinc are needed for several body activities, such as organ functions andbiological chemical processes. Within these tests, we employed analysis of liver enzyme, urea, and creatinine,to discover the damaged tissue causing after exposure to heavy metals. Results of liver function enzymes,Aspartate aminotransferase (AST), Alanine transaminase (ALT), and Alkaline phosphatase (ALP), wereregistered a significantly increasing (P?0.05) for control, Cadmium treatment and zinc treatment groups,with (32.1, 39.3, and 30.5) IU/ml, (9.6, 16.0, and 8.4) IU/ml, and (1.6, 2.5 and 2.12) IU/ml, respectively.Cadmium administration was significantly reduced (P?0.05) in serum creatinine concentration (1.26) IU/ml, compared to the control group (2.02) IU/ml. While the average serum creatinine concentration increasedto (4.99) IU/ml after giving rat group Zinc solution. Moreover, the urea concentration was significantlydecreased to (18.85) IU/ml in the Cadmium treatment group than values of control and Zinc group (30.61,and 35.97) IU/ml, respectively.